The threat of invasive species to IUCN-listed critically endangered species: A systematic review - Dueñas, Manuel-Angel; Hemming, David J.; Roberts, Amy; Diaz-Soltero, Hilda (Global ecology and conservation, 2021)
We conducted a comprehensive review of the research literature on interactions between invasive species and species included in the critically endangered category of the International Union for Conservation of Nature (IUCN) Red List. This review reveals that, globally, invasive species threaten 14% (28% on islands) of critically endangered terrestrial vertebrate species (birds, mammals and reptiles), with critically endangered birds (25%; 47% on islands) the most affected, threatened predominantly by a few invasive mammal predators (mainly rodents and feral cat). The chytrid fungal pathogen is the main threat for critically endangered amphibians. The control and management of the invasive species identified in this study should be a high priority for global biological conservation, thereby contributing towards the achievement of the goals of the Post-2020 Framework of the Convention on Biological Diversity. Further research on the impacts of invasive species and interactions with other drivers will be essential for the conservation of highly threatened species.